2017
DOI: 10.1080/1612197x.2017.1321030
|View full text |Cite
|
Sign up to set email alerts
|

The intention-behaviour gap: An empirical examination of an integrative perspective to explain exercise behaviour

Abstract: This study tested the Theory of Planned Behavior (TPB) in conjunction with two sets of variables from the Health Action Process Approach (HAPA) and the Subjective Exercise Experience Scale (SEE) to predict exercise behavior. This study included 454 participants who exercised in a fitness center. We collected measures of the TPB (attitudes, subjective norms, perceived behavioral control, and intention), HAPA (planning), and SEE (positive wellbeing, psychological distress, and fatigue) and assessed exercise beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 60 publications
1
19
1
4
Order By: Relevance
“…Intention on present participants in a 1-year longitudinal design displayed variance of only 5 percent on future behavior. These results are quite below the 11 percent observed by Gomes et al (2017) or the 20 to 30 percent interval identified by Hagger and Chatzisarantis (2009). Current results could be explained by the exercise experience gym members already had.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Intention on present participants in a 1-year longitudinal design displayed variance of only 5 percent on future behavior. These results are quite below the 11 percent observed by Gomes et al (2017) or the 20 to 30 percent interval identified by Hagger and Chatzisarantis (2009). Current results could be explained by the exercise experience gym members already had.…”
Section: Discussioncontrasting
confidence: 65%
“…Gym entries were summed up into two scores, one for the 6 months adherence prior to filling the questionnaires and one after 6 months of regular exercise. Similar procedures have been used in the literature (Gomes et al, 2017) and observable measures are more reliable than self-reported questionnaires (Liu et al, 2016).…”
Section: Enjoyment the Physical Activity Enjoymentmentioning
confidence: 99%
“…Past experience (gym entries six months before the initial assessment) and future exercise adherence (gym entries six months after the initial assessment) were considered for analysis. Similar procedures have already been used in the same context [11], when authors considered gym attendance records as an observable measure of behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Among various contemporary theories, the Self-Determination Theory (SDT) [9] stands out as one of the most studied frameworks in the exercise context [10]. This model considers motivational factors as agents for cognitive and behavioral outcomes, such as exercise commitment [11,12]. Central to SDT is the distinction between autonomous motivation, which refers to the experience of personal choice and autonomy, feeling that people's actions represent their true self; and controlled motivation, which represents a feeling of being controlled, pressured or coerced into behaving according to external or self-imposed contingencies.…”
Section: Theoretical Framework In the Exercise Contextmentioning
confidence: 99%
“…De facto, e considerando a Teoria Comportamento Planeado (que é um dos modelos mais referenciados neste domínio), os resultados têm vindo a demonstrar que a relação entre a intenção de praticar EF e o comportamento efetivo de EF é na ordem dos 45% de variância explicada para a intenção de prática de EF, mas estes valores reduzem-se significativamente para 20% quando se trata de explicar o comportamento efetivo de EF (ver Hagger, Chatzisarantis, & Biddle, 2002). Estudos mais recentes têm vindo igualmente a obter uma menor percentagem de variância explicada da prática de EF relativamente à intenção de prática de EF (ver Gomes, Gonçalves, Maddux, & Carneiro, 2017;Gucciardi & Jackson, 2015). A este fenómeno de baixa relação entre intenção e o comportamento efetivo de EF designou-se por "intention-behaviour gap" (Armitage, 2005;Courneya, 1995), existindo um interesse na 4 | R Morais, AR Gomes literatura em analisar que outros fatores podem ajudar a explicar a relação entre a intenção das pessoas praticarem EF e o comportamento efetivo de EF.…”
Section: Fatores Promotores Do Exercício | 3 Introduçãounclassified